TYPES OF BANK LOANS AND THEIR IMPACT ON ECONOMIC DEVELOPMENT: A CASE STUDY OF THE CZECH REPUBLIC - Černohorský, Jan (My University, 2017)
This article aims to evaluate the impact of the development of different types of loans in the banking sector on economic development. We will begin with the hypothesis that economic performance increases with the growth of the rate of various types of loans. We will first look at research of current scientific knowledge in respect to bank loans and economic development. The basic idea of this article is the hypothesis described above, determined on the basis of standard economic findings and based on the results of a majority of related studies. The development of loans provided can be quantified based on data from the Czech National Bank as total loans and divided into loans to non-financial companies and households, as well as mortgage loans and consumer loans. The development of the economy can also be quantified using data from the Czech Statistical Office on the development of the gross domestic product. The period selected is the years 2004-2015. To determine the relationships between selected variables, we have used statistical methods that respect the specific characteristics of the selected time series, namely the Engle-Granger causality test. Prior to testing, it was necessary to adjust the data as stationary and then test cointegration. An optimum order delay was also determined using the Akaike information criterion. The calculated results, except for consumer loans, confirm the hypothesis regarding the positive impact of the rate of loans provided on economic growth, particularly with a six-month time lag. We have obtained results that correspond to standard economic knowledge and results of most previous studies.
Druhy bankovních úvěrů a jejich vliv na vývoj ekonomiky: případová studie České republiky
Keywords: Banks, Bank Loans, Economic Cycle, Engle-Granger Causality; banky, bankovní úvěry, hospodářský cyklus, Engle-Grangerova kauzalita